The Effectiveness of New Intermediate Care Rehabilitation Network Model in Stroke Patients of Muang District, Chiangrai Province - Sumanapun, Nutthakun (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
This retrospective cohort study included stroke patients treated at Chiang Rai Prachanukroh Hospital who completed six months of intermediate rehabilitation or achieved an MBI score of 20 earlier. Participants were divided into two groups: a new rehabilitation group of 242 people and a traditional rehabilitation group of 318 people. Participants had at least two MBI assessments: at hospital discharge and post-rehabilitation. Exclusion criteria were death within six months post-diagnosis or unavailable medical records. Data was collected using Microsoft Excel. The research instruments used were electronic medical records and the Thai version of the Modified Barthel Index (ICC = 0.87). Data were analyzed using descriptive statistics, exact probability test, t-test, Wilcoxon signed-rank test, and linear regression. Both groups showed significant MBI improvements post-treatment (p < 0.00). Service utilization including physical therapy, occupational therapy, home visits, private clinic services, and hospital visits was significantly higher in the 2024 group (p < 0.05). Baseline differences were observed in hypertension, dyslipidemia, and stroke etiology. After adjusting for these factors, differences in functional improvement (∆MBI) between the models were not statistically significant. The new model enhanced access to care and treatment intensity through public-private collaboration. However, functional outcomes were comparable to the traditional model when accounting for baseline characteristics. Future prospective randomized controlled trials are recommended to reduce confounding and more accurately assess intervention effectiveness.